Sinhrono-diahroni pregled krajšav v slovenskem prostoru in sestava slovarja krajšav - Kompara, Mojca (2018)
Synchronic and Diachronic Overview of Abbreviation in Slovene and the Compilation of the Dictionary of Abbreviations. The author presents the position of abbreviations in Slovene, highlights the need of a dictionary of abbreviations, and presents the guidelines for obtaining the compilation material and the dictionary article of the new dictionary of abbreviations on a diachronic and synchronic level.  The monograph consists of nine chapters where the classification of abbreviations and the position of abbreviations in Slovene orthographic dictionaries from 1899 to 2001 and selected language manuals are presented. The detailed position of abbreviations in general and specialized dictionaries, in terms of micro- and macrotexture, as well as the dictionaries of abbreviations from 1948, 2006 and 2011 are presented. The algorithm for automatic recognition of abbreviations and expansions, and algorithms prepared between 1999 and 2016 are presented through systematic compilation of abbreviations. The author outlines the need of a modern dictionary of abbreviations and presents the dictionary article of the new dictionary of abbreviations.
Keywords: dictionary; abbreviation; algorithm; lexicography; dictionary of abbreviations